Formulation and optimisation of raft‑forming chewable tablets containing H2 antagonist - Prajapati, Shailesh T; Mehta, Anant P; Modhia, Ishan P; N Patel, Chhagan (International Journal of Pharmaceutical Investigation)
Purpose: The purpose of this research work was to formulate raft‑forming chewable tablets of H2 antagonist (Famotidine) using a raft‑forming agent along with an antacid‑ and gas‑generating agent. Materials and Methods: Tablets were prepared by wet granulation and evaluated for raft strength, acid neutralisation capacity, weight variation, % drug content, thickness, hardness, friability and in vitro drug release. Various raft‑forming agents were used in preliminary screening. A 23 full‑factorial design was used in the present study for optimisation. The amount of sodium alginate, amount of calcium carbonate and amount sodium bicarbonate were selected as independent variables. Raft strength, acid neutralisation capacity and drug release at 30 min were selected as responses. Results: Tablets containing sodium alginate were having maximum raft strength as compared with other raft‑forming agents. Acid neutralisation capacity and in vitro drug release of all factorial batches were found to be satisfactory. The F5 batch was optimised based on maximum raft strength and good acid neutralisation capacity. Drug–excipient compatibility study showed no interaction between the drug and excipients. Stability study of the optimised formulation showed that the tablets were stable at accelerated environmental conditions. Conclusion: It was concluded that raft‑forming chewable tablets prepared using an optimum amount of sodium alginate, calcium carbonate and sodium bicarbonate could be an efficient dosage form in the treatment of gastro oesophageal reflux disease.
Keywords: Acid neutralisation capacity; famotidine; raft‑forming agent; raft strength; sodium alginate; texture analyzer